De porto a porto :o eldorado brasileiro na percepção dos imigrantes haitianos em Porto Velho-RO - Gottardi, Ana Paula Pellegrino (2015)
In Brazil several migratory flows have occurred, over the progression of its economic development, since the period of colonization until today. Immigrants from various parts of the world have found their way crossing our borders in search of work such as Europeans, Asians, and, recently, a great wave of Bolivians, Senegalese and Haitians. The Haitians are the subject of this study, which aims to analyze the migratory insertion of these persons in terms of expectations and experiences in the city of Porto Velho-RO; profiling these people; identifying the reasons that forced them to leave Haiti; describing the elements that constitute its expectation in Brazil and the verification of the relationship between initial expectations and the current experience of migration they had undertaken. The interest in this matter is related to the increasing migratory wave of Haitians that began after the earthquake that struck Haiti in 2010; further exacerbating the problems faced by this country. In this sense, the subject is justified because of the utmost importance for a discussion that may contribute to the enhancement of immigration policy in Brazil, as the current legislation is wrong, making a better reception of immigrants in national territory, as well as their social insertion. A brief historical overview of Haiti is redeemed to understand the situation and socio-economic policy historically constructed in the country and its relations with the migration process. The main currents and flows of immigration of Haitians to various destinations of the globe were surveyed; in order to show the frequency of these practices and the recent route to Brazil, the research was carried out in a qualitative, exploratory, with documentary analysis and field survey, with semi-structured interviews the 05 Haitians, of both sexes, immigrants, residents of Porto Velho, RO, in that oral history was used as methodology of apprehension and record the narratives of the participants. The verbal emissions were handled by Content Analysis; the reports collected among both immigrants and media, in addition to research and data from government agencies served as a basis for the understanding of the process of arrival and insertion of the Haitian community in Brazil, its main destinations and conditions of life and work.